The Norton anthology of English literature. The major authors - Abrams, M. H., (Meyer Howard), 1912-; Greenblatt, Stephen, 1943- (New York : Norton, 2001)
Provides a representive selection of writings, in diverse literary genres, of major English authors, from the Middle Ages through the twentieth century; and includes selected bibliographies, geographic nomenclature, and other reference aids, as well as an index.
Map on endpapers.
Includes bibliographical references and index.
Reference and Research Book News.
Adult
Keywords: English literature; English literature; Great Britain -- Literary collections; Great Britain -- Literary collections